IL-7 producing immunotherapy improves ex vivo T cell functions of immunosenescent patients, especially post hip fracture - Chrystel Marton; Alix Minaud; Charles-Antoine Coupet; Manon Chauvin; Jamila Dhiab; Hélène Vallet; Jacques Boddaert; Nadine Kehrer; Bérangère Bastien; Geneviève Inchauspe; Luc Barraud; Delphine Sauce (Taylor & Francis Group, 2023)
Following acute stress such as trauma or sepsis, most of critically ill elderly patients become immunosuppressed and susceptible to secondary infections and enhanced mortality. We have developed a virus-based immunotherapy encoding human interleukin-7 (hIL-7) aiming at restoring both innate an adaptative immune homeostasis in these patients. We assessed the impact of this encoded hIL-7 on the ex vivo immune functions of T cells from PBMC of immunosenescent patients with or without hip fracture. T-cell ex vivo phenotyping was characterized in terms of senescence (CD57), IL-7 receptor (CD127) expression, and T cell differentiation profile. Then, post stimulation, activation status, and functionality (STAT5/STAT1 phosphorylation and T cell proliferation assays) were evaluated by flow cytometry. Our data show that T cells from both groups display immunosenescence features, express CD127 and are activated after stimulation by virotherapy-produced hIL-7-Fc. Interestingly, hip fracture patients exhibit a unique functional ability: An important T cell proliferation occurred compared to controls following stimulation with hIL-7-Fc. In addition, stimulation led to an increased naïve T cell as well as a decreased effector memory T cell proportions compared to controls. This preliminary study indicates that the produced hIL-7-Fc is well recognized by T cells and initiates IL-7 signaling through STAT5 and STAT1 phosphorylation. This signaling efficiently leads to T cell proliferation and activation and enables a T cell "rejuvenation." These results are in favor of the clinical development of the hIL-7-Fc expressing virotherapy to restore or induce immune T cell responses in immunosenescent hip fracture patients.